Fate breaker - Aveyard, Victoria (Aveyard, Victoria. Realm breaker series, 2024)
"Armed with Taristan's sword, the only Spindleblade left in existence, Corayne must stop him and Queen Erida from bringing forth their demon god to destroy the world"--